2015
DOI: 10.5688/ajpe797101
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Determinants of Academic Performance in Nigerian Pharmacy Schools

Abstract: Objective. To evaluate cognitive factors that might influence academic performance of students in Nigerian pharmacy schools. Methods. A cross-sectional, multi-center survey of Nigerian pharmacy students from 7 schools of pharmacy was conducted using 2 validated questionnaires measuring cognitive constructs such as test anxiety, academic competence, test competence, time management, and strategic study habits. Results. Female students and older students scored significantly better on time management skills and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(31 reference statements)
1
9
0
1
Order By: Relevance
“…16 Many studies have found that test anxiety and academic performance have a significant negative association. 17,18 State anxiety was found to be elevated during the OSCE, written test, and preclinical preparation test, and the OSCE was revealed to be the most anxiety-provoking assessment method. 9 Moreover, lower levels of state and trait anxiety have been identified as factors that improve OSCE performance.…”
Section: Introductionmentioning
confidence: 99%
“…16 Many studies have found that test anxiety and academic performance have a significant negative association. 17,18 State anxiety was found to be elevated during the OSCE, written test, and preclinical preparation test, and the OSCE was revealed to be the most anxiety-provoking assessment method. 9 Moreover, lower levels of state and trait anxiety have been identified as factors that improve OSCE performance.…”
Section: Introductionmentioning
confidence: 99%
“…Test anxiety was negatively associated with academic performance (Ubaka, Sansgiry, & Ukwe, 2015) and with self-regulated learning strategy (Ning & Downing, 2015), but was positively associated with adaptive coping strategies (Kondo, 1997) and with proactive coping (Raffety, Smith, & Ptacek, 1997). Additionally, worry and emotionality, major components of test anxiety, were positively associated with emotion-focused coping (Zeidner, 1996), and worry was negatively associated with problemfocused coping (Zeidner, 1996).…”
mentioning
confidence: 88%
“…[2][3][4][5][6][7][8][9] Current literature in higher education suggests that nonperformance-based factors, such as self-efficacy, test anxiety, engagement in co-curricular activities, low levels of academic entitlement, and personality may be associated with academic achievement. 4,[10][11][12][13] Multiple methods for characterizing personality have been developed and used to evaluate academic performance. 14,15 Multiple studies in undergraduate students use the "Big Five" personality trait framework, which characterizes essential personality traits of agreeableness, conscientiousness, extraversion, neuroticism, and openness.…”
Section: Introductionmentioning
confidence: 99%